Peace Psychology in Asia 2009
DOI: 10.1007/978-1-4419-0143-9_3
|View full text |Cite
|
Sign up to set email alerts
|

Where Are We Going? Perspective on Hindu–Muslim Relations in India

Abstract: The twin issues of making peace and building it over time, which are very much at the forefront of social concerns in contemporary India, remain a major source of worry and require a thoughtful understanding. The lack of effort that has been dedicated towards the development of a systematic understanding of the psychological dynamics underpinning intergroup hostility and violence between Hindus and Muslims in India is disappointing to say the least. While elaborate analyses and accounts of these intergroup dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…From the perspective of collective victimhood research (for reviews, see Noor et al, ; Vollhardt, ) that has taken a single‐identity approach and assessed relations between groups (e.g., ethnic, religious, or national), our intersectional approach revealed that these beliefs were also relevant at a within‐group level. This is noteworthy because ongoing threat and victimization can make group members focus more on ingroup unity, and the political discourse in postindependence India has pitted one community against the other and homogenized single‐group social identities (Khan & Sen, ). Moreover, our findings suggest that comparisons between communities may not be the only or most meaningful focus of analysis—especially when intragroup differences are leveraged to polarize different intersections within a community.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the perspective of collective victimhood research (for reviews, see Noor et al, ; Vollhardt, ) that has taken a single‐identity approach and assessed relations between groups (e.g., ethnic, religious, or national), our intersectional approach revealed that these beliefs were also relevant at a within‐group level. This is noteworthy because ongoing threat and victimization can make group members focus more on ingroup unity, and the political discourse in postindependence India has pitted one community against the other and homogenized single‐group social identities (Khan & Sen, ). Moreover, our findings suggest that comparisons between communities may not be the only or most meaningful focus of analysis—especially when intragroup differences are leveraged to polarize different intersections within a community.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it is not inevitable that people express intersectional consciousness about their group's collective experiences of victimization. Indian political discourse since independence has led to homogenization along caste and religious lines, for example, by reinforcing existing stereotypes (Khan & Sen, ). Further, conflict and external threat (e.g., by Hindu fundamentalists) can enhance social cohesion and perceived intragroup similarities that mobilize group members to participate in actions defending or strengthening the ingroup (Bar‐Tal, ; Wohl et al, ).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Their share in the population varies considerably across states, ranging from close to zero to more than 60 percent in the only Muslim-majority state of Jammu and Kashmir. Conflict between these two groups related to social, political, economic and religious issues are well documented in literature (Ghosh, Kumar, & Tripathi, 1992;Kakar, 1996Kakar, , 2000Kausar, 2006;Khan & Sen, 2009;Mishra, Akoijam, & Mishra, 2009;Mitra & Ray, 2014;Platow et al, 2013).…”
Section: Justice Perception and Intergroup Relationsmentioning
confidence: 99%
“…This lacuna is paralleled with a general lack of social and political psychological research addressing pertinent societal issues in India. For example, research into the culture-specific context and nature of ideology along the political spectrum in India does not exist, and with the exception of only very few studies, research into intergroup relations tends to be decontextualised (for an overview, see Khan & Sen, 2009). This signals significant scope for social and political psychology to make There are multiple avenues that lend themselves to social and political psychological research -the greater point being made here is that the discipline(s) is theoretically and methodologically equipped to make important contributions towards better understanding political, identity, and intergroup dynamics in India, insofar as it takes into account the context of these dynamics in calibrating its research questions.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%